Clinical Profile, Cardiac Manifestations, And Outcomes Of Hospitalised Patients With Scrub Typhus: A Cross-Sectional Observational Study At A Tertiary Care Hospital. - Rao Tati, Srinivasara; Avinash S, Avinash S (Journal of Neonatal Surgery, 2025)
Background: Scrub typhus, caused by Orientia tsutsugamushi, is an important but underdiagnosed rickettsial disease in South and Southeast Asia. Cardiac involvement, including myocarditis and pericardial effusion, is an underappreciated complication contributing to excess morbidity and mortality. Systematic data on the cardiac spectrum and its predictors are scarce from Indian tertiary care hospitals. Methods: This cross-sectional observational study enrolled 250 hospitalised adults with confirmed scrub typhus (IgM ELISA positive against O. tsutsugamushi; Weil-Felix OXK titre ≥1:80 supportive) at a tertiary care hospital over 24 months. Clinical features, organ-system involvement, ECG, echocardiography, cardiac biomarkers (troponin-I, NT-proBNP), and outcomes were documented. Results: Eschar was identified in 42.0% of patients. Thrombocytopenia was present in 73.2%, hepatic involvement in 81.2%, acute kidney injury in 28.4%, and ARDS in 19.2%. Cardiac involvement (any) was documented in 31.2%: sinus tachycardia 22.4%, prolonged QTc 8.0%, myocarditis (LVEF <50%) 11.2%, pericardial effusion 14.4%. In-hospital mortality was 7.2%. Multivariable predictors of mortality included presentation delay >7 days, ARDS, echocardiographic myocarditis, and APACHE-II >15. Conclusion: Cardiac involvement is common in scrub typhus, present in nearly one-third of hospitalised patients. Myocarditis and pericardial effusion are significant contributors to morbidity and mortality. Routine ECG and echocardiography are recommended for all hospitalised scrub-typhus patients...